2021
DOI: 10.1155/2021/9921094
|View full text |Cite|
|
Sign up to set email alerts
|

Perioperative Nursing Care of Vascular Decompression for Trigeminal Neuralgia under AR Medical Technology

Abstract: AR technology, also known as AR or virtual reality, refers to a technology that combines and allows interaction of the virtual world on the display system with the real world through the position and angle of the camera video and image analysis technology. This technology is different from VR technology, and its characteristics can be easily explained as follows: when using AR technology, the user’s eyes can see not only the real world but also the virtual world derived from the computer through things in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…e high blood glucose of diabetic patients with traumatic calcaneal fractures may retard fracture healing, and the patients are predisposed to postoperative complications such as incisional infections, which compromise the recovery of foot function and the quality of life of the patients [1][2][3]. It has been suggested that the combination of perioperative targeted therapeutic interventions contributes to reducing postoperative complications and shortening the recovery time [4,5]. To this end, this study was conducted to assess the efficacy of targeted treatment in the perioperative management of diabetic patients with traumatic calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…e high blood glucose of diabetic patients with traumatic calcaneal fractures may retard fracture healing, and the patients are predisposed to postoperative complications such as incisional infections, which compromise the recovery of foot function and the quality of life of the patients [1][2][3]. It has been suggested that the combination of perioperative targeted therapeutic interventions contributes to reducing postoperative complications and shortening the recovery time [4,5]. To this end, this study was conducted to assess the efficacy of targeted treatment in the perioperative management of diabetic patients with traumatic calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Perioperative Nursing Care of Vascular Decompression for Trigeminal Neuralgia under AR Medical Technology” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%